Nexus Between Artificial Intelligence Technology and General Election Principles: Opportunities and Challenges - Rofi Aulia Rahman Rofi; Hesti Armiwulan Hesti; Valentino Nathanael Prabowo Valentino (Asia-Pacific Journal of Elections and Democracy, 2023)
Artificial intelligence (AI) technology influences the practice of elections in many countries since AI technology can influence a country's electoral result and process, as was the case in the 2016 U.S. presidential election, in which Donald Trump ended up winning. The use of AI technology in campaign activities that can effectively convince voters to vote for Trump is one of the reasons for his triumph. This event is also inextricably linked to AI-influenced election tactics in Indonesia, such as the deployment of bot accounts and deep fakes during the election. This situation occurred as a result of the election candidates' usage of AI technology. Such misuse of AI generates democratic challenges, specifically unfair elections. Therefore, it is necessary to create a robust framework to govern AI technology and its use in the Indonesian electoral process. The article addresses the following issues: (a) the development of AI technology and its nexus to elections; (b) the impact of AI technology on the election principles; (c) the urgency of regulating AI in elections; and (d) the opportunities and challenges of regulating AI technology in Indonesia's legal system. The article concludes that AI technology continues to pose a threat to democratic election principles if Indonesia does not provide sufficient legal instruments to address issues arising from the misuse of AI technology in Indonesia's election process.